Prenatally detected copy number variants in a national cohort: A postnatal follow‐up study. (24th June 2020) - Muys, Joke; Jacquemyn, Yves; Blaumeiser, Bettina; Bourlard, Laura; Brison, Nathalie; Bulk, Saskia; Chiarappa, Patrizia; De Leener, Anne; De Rademaeker, Marjan; Désir, Julie; Destrée, Anne; Devriendt, Koenraad; et al.
Abstract: Objective: Belgian genetic centers established a database containing data on all chromosomal microarrays performed in a prenatal context. A study was initiated to evaluate postnatal development in children diagnosed prenatally with a non‐benign copy number variant (CNV). Methods: All children diagnosed with a prenatally detected non‐benign CNV in a Belgian genetic center between May 2013 and February 2015 were included in the patient population. The control population consisted of children who had undergone an invasive procedure during pregnancy, with no or only benign CNVs. Child development was evaluated at 36 months using three (3) questionnaires: Ages and Stages Questionnaire Third edition, Ages and Stages Questionnaire Social‐Emotional Second Edition and a general questionnaire. Results: A significant difference in communication and personal‐social development was detected between children with a reported susceptibility CNV and both children with an unreported susceptibility CNV and the control population. The outcome of children with a particular CNV is discussed in a case‐by‐case manner. Conclusion: Our postnatal follow‐up project of children with a prenatally detected non‐benign CNV is the first nationwide project of its kind. A higher number of cases for each CNV category is however needed to confirm our findings.